Adherence to Iron, Folic Acid and Calcium Supplement and Factors Affecting it among the Antenatal Care Attending Women in a Tertiary Care Hospital: A Cross Sectional Study - Shakya Shrestha, S.; Adhikari, R.; Tamrakar, S.; Shrestha, R.; Shrestha, A. (Kathmandu University Medical Journal, 2020)
Background Pregnancy or gestation is the time during which a single or more children grows and develops inside a woman. Antenatal care improves the pregnancy outcomes under which a group of medication i.e. iron, folic acid and calcium are supplemented. Despite the effectiveness of such supplements, poor clinical outcomes are often encountered because of poor-adherence to the regimen. Objective To determine the adherence pattern and factors affecting adherence in antenatal care patients under iron, folic acid, and calcium therapy. Method A cross-sectional study was conducted in Dhulikhel Hospital, Kathmandu University Hospital. Pregnant women attending antenatal care under iron, folic acid, and calcium therapy fulfilling the inclusion criteria were enrolled in this study. After obtaining the informed consent from the patients, structured questionnaire was used to interview the patients. Statistical analysis was performed by using SPSS 23.0. P-value < 0.05 was considered as statistically significant. Result Among 191 patients enrolled in this study majority (39.3%) of them belonged to age group 26-30 years. More than half (61.3%) of the patients were illiterate. Of the total 191, 64.40% were non-adherent to the medication. Forgetfulness was the main reason for missing the dose in majority (52.06%) of the non-adherent subjects while adverse effects (55.40%) was the most prominent cause for discontinuing the medication among non-adherent participants. Significant association was found between patients’ adherence and busy work schedule, visiting doctor for follow up. Conclusion More than half of the patients had not adhered to the medication under antenatal care. Forgetfulness was the most common factor for missing the dose in nonadherent patients. Illiteracy was associated with poor adherence. Patient-provider relationship, Socio-economic factors were determined as major barrier to medication adherence.